The roles of mycotoxins in cereal crops production: A comparative study of Hungary and Tanzania - Nyandi, Muhoja Sylivester; Pepó , Péter (Acta Agraria Debreceniensis, 2022)
Although Hungary and Tanzania’s climatic, soil, and technological conditions differ significantly in crop production, cereals crop cultivation is of paramount importance; maize crop dominates the cultivated area (Hungary 1 million ha, Tanzania 3 million ha) both from a feed and food point of view. Unfortunately, in both countries, fungal species (Fusaria, Aspergilli, Penicillia, etc.) that produce various mycotoxins on cereals, including maize grains, are a growing concern. The situation is complicated because these fungal species and their toxins can appear not only on cereals but also on other crops. Despite the prevalence of mycotoxins in both countries, studies show higher exposure risks and contamination above tolerable levels for human consumption in Tanzania to Hungary, with Tanzania observing acute aflatoxicosis.